PUBLIC PARTICIPATION URGENCY AS A EFFORTS AND REQUIREMENTS FOR THE FORMATION OF GOOD LAW - Anggono, Bayu Dwi; Firdaus, Fahmi Ramadhan (Faculty of Law, Universitas Jenderal Soedirman, 2021)
One of the requirements for a good law is participatory, this is needed in the hope that the law can be effectively implemented, because the aspirations of the needs of the public have been accommodated. However, it is not uncommon for the process of establishing laws in Indonesia to be considered to be less participatory. Although there is public participation, it is considered a formality and the people's aspirations are not substantially stated in the law. The problem discussed in this paper is, how a good law product should be and whether the urgency of public participation involvement in the formation of laws. The method of approach used in this paper is the conceptual approach, based on the concept of a democratic rule of law. In addition, this paper uses a comparative approach method, which compares and studies the involvement of public participation in the process of forming laws in several countries. This paper provides an overview of a good law product and the importance of public participation as an effort to form a good and effective law.Keywords: Laws and Regulations; Rule of Law; Public Participation